The Value of Islamic Education in The Nahu Sanamang Tradition at Negeri Tulehu - Umarella, Samad Umarella; Hamka, Syamsuar Hamka (IAIN Ambon, 2023)
The problem in this research is how to implement the Nahu Sanamang tradition in Negeri Tulehu, Salahutu District, Central Maluku Regency and the values of Islamic education in that tradition. The type of research used is qualitative research, by using an ethnographic approach. The techniques used including observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclution. The results of the research on the implementation of the Nahu Sanamang tradition were carried out at the house of the man who was getting married, starting with a proposal containing determining the number of assets and determining the day for carrying out the Nahu Sanamang tradition, followed by the preparation process until the closing of the implementation of the tradition. Nahu Sanamang itself was born as a forum for brotherly ties for all the people of Negeri Tulehu to work hand to lighten the burden on families who are going to get married. The values of Islamic education in the Nahu Sanamang tradition in Negeri Tulehu, Salahutu District, and Central Maluku Regency reflect a good that must be done in part from the values of aqeedah or belief, alms values, silaturrahim values, tolerance values, and helpful values as a means of strengthening kinship relation between communities in Negeri Tulehu.